Decades of practical experience and network theory - Doris Marquardt (Economics and Rural Development, 2013)
Funded “Networking” has steadily gained importance among European Union (EU) rural policies instrumentation: Since 1991, with LEADER the formation of regional public-private partnerships and EU-wide information exchange has been supported. Later also inter-territorial cooperation was funded. Additionally, National Rural Networks interlinked at the European level and associating the implementation of rural interventions have recently been established. Networking activities are acknowledged as drivers for rural development. While it is true that good practices are assiduously collected, the deficit in systematically scrutinizing networking activ-ities and their underlying causal patterns is only filled by the present research. Applying network theory, the concept of social capital and transaction-costs considerations, this paper strives to investigate the relevance of financial support for networking, and whether the potential that networking theoretically offers could be exploited more sufficiently. In addition to its unique approach, the empiri-cal data underlying this research presents a novelty, as the various stakeholders surveyed across the EU in the period 2008-2010 in-clude potential LAGs and the newly established rural networks. Reviewing the literature and survey results, determinants for using the potential of networking interventions are identified, and the effects of different types of networking are discussed against finan-cial, technical and social inputs. The results reveal significant contributions that sociology can make to public policies, and can allow conclusions about designing external support to networking. The findings highlight that: 1) funding networking can be meaningful; 2) strongly funded networks tend to fail to create added value; 3) networking needs endogenously grown objectives; and 4) support-ing networking between regions technically is preferable to funding inter-regional partnerships.
Keywords: R30; R38; D85; H49; 330; networking; rural development policies; network theory; European Union; national rural networks